Managerial style and well‐being among psychiatric nurses: A prospective study. Issue 7 (27th August 2019) - Gillet, Nicolas; Le Gouge, Amélie; Pierre, Rémi; Bongro, Justin; Méplaux, Véronique; Brunault, Paul; Guyetant, Sophie; Fremont, Catherine; Camus, Vincent; Colombat, Philippe; Fouquereau, Evelyne; Cheyroux, Pierre
Accessible summary: What is known on the subject?: Numerous studies have shown that organizational and managerial factors have significant effects on nurses' workplace well‐being. There are few studies on the effects of nurses' perceptions of their supervisors' autonomy‐supportive behaviours on their workplace well‐being. There are few studies on the determinants of nurses' workplace well‐being within a psychiatric context. What does this paper add to existing knowledge?: This study examines the psychological processes underlying the relationship between nurses' perceptions of their supervisors' autonomy‐supportive behaviours and their workplace well‐being. Mental health nurses' perceptions of their supervisors' autonomy‐supportive behaviours are indirectly and positively related to their workplace well‐being through their positive effects on psychological need satisfaction. Autonomy and competence need satisfaction has stronger effects on workplace well‐being than relatedness need satisfaction. What are the implications for practice?: When their supervisor gives nurses a meaningful rationale for tasks and acknowledges their feelings and views, they feel more autonomous, competent and related to others. It is important for nurses to feel autonomous and competent in order to experience well‐being at work. Nurses' workplace well‐being might be positively and negatively linked to quality of care and turnover intentions, respectively. Abstract: Introduction: There is growing interest in the relationships between work factors and nurses' workplace well‐being. However, there has been very little research on the psychological processes underlying the relationships between nurses' perceptions of supervisors' autonomy‐supportive managerial style and their workplace well‐being. Aim/question: Drawing on self‐determination theory, we explored the mediating role of psychological need satisfaction (autonomy, competence and relatedness) in the relationships between nurses' perceptions of supervisors' autonomy‐supportive managerial style and their workplace well‐being, using a prospective design. Method: A prospective questionnaire was given to nurses in eight French psychiatric units. Data were collected from a sample of 294 French nurses who completed measures of perceived supervisors' autonomy‐supportive behaviours at Time 1 and of psychological need satisfaction, work engagement and job satisfaction at Time 2 one year later. Results: Results revealed that nurses' perceptions of supervisors' autonomy‐supportive managerial style were indirectly and positively related to their vigour, dedication, absorption and job satisfaction one year later through their positive effects on psychological need satisfaction. Discussion/implications for practice: Overall, this paper sheds light on the indirect effect of nurses' perceptions of supervisors' autonomy‐supportive behaviours on their workplace well‐being. Theoretical contributions and future directions, as well as implications for practice, are discussed.